Varnost in zdravje pri pridobivanju, predelavi in rabi lesnih goriv - Dolenšek, Marjan (Gozdarski vestnik, 2016)
With increasing use of wood fuels and enlarged size of work in forests also the number of dangers and incidents at this work increases. Making people aware of actions which will ensure safe and health non-damaging production and use of wood fuels is essential.
Keywords: lesna goria; pridobivanje lesnih goriv; raba lesnih goriv; varstvo pri delu